Long-term administration of protein hydrolysate from chicken feet induces antihypertensive effect and confers vasoprotective pattern in diet-induced hypertensive rats. (April 2019) - Mas-Capdevila, Anna; Iglesias-Carres, Lisard; Arola-Arnal, Anna; Suarez, Manuel; Muguerza, Begoña; Bravo, Francisca I.
Graphical abstract: Highlights: Chicken feet as a high-quality peptide new source for functional foods. Long-term antihypertensive effect of chicken feet hydrolysate in diet-induced hypertensive rats. Blood pressure reduction through endothelial improvement. This chicken by-product could be revalorized as an antihypertensive ingredient. Abstract: The aim of this study was to evaluate the effect of long-term administration of the protein hydrolysate from chicken feet Hpp11 in diet-induced hypertensive rats. Rats were fed standard or cafeteria (CAF) diets for 12 weeks, and during the final 3 weeks, CAF animals were administered vehicle, Captopril or Hpp11. Systolic blood pressure (SBP) was recorded weekly. Body weight and plasmatic lipid and glucose levels were determined. Moreover, liver-reduced glutathione (GSH) levels, plasmatic angiotensin converting enzyme (ACE) activity and the endothelial gene expression of eNOS, KLF-2, Sirt-1, NOX4 and ET-1 were studied. A definite decrease in SBP was recorded in the rats that were administered Hpp11. Hpp11 downregulated gene expression of the vasoconstrictor ET-1 and induced the upregulation of NOX4 and NO enhancer Sirt-1, suggesting the vasoprotective effect of Hpp11. Moreover, Hp11 increased hepatic GSH. The present findings suggest that Hpp11 is a good candidate to ameliorate diet-induced hypertension.